Pharmacological HIF‐PHD inhibition reduces renovascular resistance and increases glomerular filtration by stimulating nitric oxide generation. (15th May 2021) - Burmakin, Mikhail; Fasching, Angelica; Kobayashi, Hanako; Urrutia, Andrés A.; Damdimopoulos, Anastasios; Palm, Fredrik; Haase, Volker H.
Abstract: Aim: Hypoxia‐inducible factors (HIFs) are O2 ‐sensitive transcription factors that regulate multiple biological processes which are essential for cellular adaptation to hypoxia. Small molecule inhibitors of HIF‐prolyl hydroxylase domain (PHD) dioxygenases (HIF‐PHIs) activate HIF‐dependent transcriptional programs and have broad clinical potential. HIF‐PHIs are currently in global late‐stage clinical development for the treatment of anaemia associated with chronic kidney disease. Although the effects of hypoxia on renal haemodynamics and function have been studied in animal models and in humans living at high altitude, the effects of pharmacological HIF activation on renal haemodynamics, O2 metabolism and metabolic efficiency are not well understood. Methods: Using a cross‐sectional study design, we investigated renal haemodynamics, O2 metabolism, gene expression and NO production in healthy rats treated with different doses of HIF‐PHIs roxadustat or molidustat compared to vehicle control. Results: Systemic administration of roxadustat or molidustat resulted in a dose‐dependent reduction in renovascular resistance (RVR). This was associated with increased glomerular filtration rate (GFR), urine flow and tubular sodium transport rate (TNa ). Although both total O2 delivery and TNa were increased, more O2 was extracted per transported sodium in rats treated with high‐doses of HIF‐PHIs, suggesting a reduction in metabolic efficiency. Changes in RVR and GFR were associated with increased nitric oxide (NO) generation and substantially suppressed by pharmacological inhibition of NO synthesis. Conclusions: Our data provide mechanistic insights into dose‐dependent effects of short‐term pharmacological HIF activation on renal haemodynamics, glomerular filtration and O2 metabolism and identify NO as a major mediator of these effects.